2014
DOI: 10.7763/ijcce.2014.v3.365
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Bottleneck Detection for Process Planning in a FAB

Abstract: Abstract-This paper presents a detection process for bottlenecks in a wafer FAB (fabrication) using a simulation approach. In a semiconductor manufacturing industry, a Wafer FAB facility includes various equipment and wafer products. The wafer FAB has many characteristics, such as re-entrant processing flow and batch tools. The performance of a complex manufacturing system (i. e. semiconductor wafer FAB) is mainly decided by a bottleneck. In this paper, we define the problem of a bottleneck process and propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…An example of the use of shortterm data in combination with real-time data is the identification of momentary bottlenecks [24]. Yang et al [26] proposed another method using short-term data (one day) to identify short-term bottlenecks. Gopalakrishnan et al [27] demonstrated that productivity increased by approximately 5% when the momentary bottleneck was identified as the short-term maintenance priority.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An example of the use of shortterm data in combination with real-time data is the identification of momentary bottlenecks [24]. Yang et al [26] proposed another method using short-term data (one day) to identify short-term bottlenecks. Gopalakrishnan et al [27] demonstrated that productivity increased by approximately 5% when the momentary bottleneck was identified as the short-term maintenance priority.…”
Section: Literature Reviewmentioning
confidence: 99%